Bioadhesive Surfactant Systems for Methotrexate Skin Delivery - Cintra, Giovana Aparecida de Souza; Pinto, Larissa Alvarenga; Calixto, Giovana Maria Fioramonti; Soares, Christiane Pienna; Von Zuben, Eliete de Souza; Scarpa, Maria Virgínia; Gremião, Maria Palmira Daflon; Chorilli, Marlus (MDPI, 2016)
Methotrexate (MTX) is an immunosuppressive drug for systemic use in the treatment of skin diseases, however, MTX presents a number of side effects, such as hepatotoxicity. To overcome this limitation, this study developed skin MTX delivery surfactant systems, such as a microemulsion (ME) and a liquid crystalline system (LCS), consisting of a glycol copolymer-based silicone fluid (SFGC) as oil phase, polyether functional siloxane (PFS) as surfactant, and carbomer homopolymer type A (C971) dispersion at 0.5% (wt/wt) as aqueous phase. Polarized light microscopy and small-angle X-ray scattering evidenced the presence of hexagonal and lamellar LCSs, and also a ME. Texture profile and in vitro bioadhesion assays showed that these formulations are suitable for topical application, showing interesting hardness, adhesiveness and compressibility values. Rheology analysis confirmed the Newtonian behaviour of the ME, whereas lamellar and hexagonal LCSs behave as pseudoplastic and dilatant non-Newtonian fluids, respectively. In vitro release profiles indicated that MTX could be released in a controlled manner from all the systems, and the Weibull model showed the highest adjusted coefficient of determination. Finally, the formulations were not cytotoxic to the immortalized human keratinocyte line HaCaT. Therefore, these bioadhesive surfactant systems established with PFS and C971 have great potential as skin delivery systems.
Keywords: in vitro skin permeation; in vitro skin retention; liquid-crystalline systems; methotrexate; microemulsion; polyether functional siloxane